Assessing the Implementation Outcomes of Interventions to Promote Healthy Eating in Latin American Restaurants. (14th June 2022) - Dimond, Emily; Conaboy, Cara; Handley, Margaret; Huang, Terry T-K; Rose, Donald; Fuster, Melissa
Abstract: Objectives: Food away from home is of increasing importance to the nutritional quality of diets, but little attention has been paid to improving the quality of Latino-serving restaurants. This paper aims to assess implementation outcomes of interventions co-developed in two Latin American restaurants (LARs) using Human-Centered Design (HCD) and implementation science as the conceptual frameworks. Methods: Interventions to increase the existence and use of healthy menu items (HMI) were developed previously in collaboration with owners and staff of two LARs in New York City. Using HCD, the perspectives of these individuals were included in a problem-solving approach to improve both the health and profitability of menu items. Key informant interviews with these individuals (n = 3 per restaurant) were conducted to obtain qualitative insights on the acceptability, adoption, feasibility, and sustainability of these interventions, all key outcomes for successful implementation. Results: The use of HCD resulted in high acceptability among owners, but not staff. Although owners and chefs in both LARs were included in the initial HCD planning process, chefs did not feel included in follow-up planning, resulting in low acceptability. Adoption was high for all roles in both LARs. Feasibility and sustainability were high in one restaurant, but not the other. While the new HMI was sustained in the first restaurant, efforts to promote them in the second restaurant with a social media campaign were hindered by the substantial time and resources required by this activity. Conclusions: HCD helped pinpoint the specific need of each LAR and offered a way to co-develop tailored interventions to address these needs, resulting in high owner acceptability and initial adoption. The mixed results found among staff show that power dynamics among different stakeholders can influence the success of healthy eating interventions. Owners are a key stakeholder for adoption, which overrides acceptability. The mixed results by intervention regarding feasibility and sustainability revealed that activities to promote HMI, such as a social media campaign, should consider the high operational burden and resource constraints of independently-owned LARs. More work is needed to improve the feasibility of these interventions. Funding Sources: NIH/NHLBI and Tulane University.